Costs and benefits of a leaf beetle Integrated Pest Management (IPM) program. I. Modelling changes in wood volume yields from pest management. Issue 1 (2nd January 2018) - Wardlaw, T.; Cameron, N.; Carnegie, A.; Lawson, S.; Venn, T.
ABSTRACT: The Tasmanian leaf beetle Paropsisterna bimaculata is a species native to Tasmania that can cause severe defoliation of eucalypt plantations. High populations of P. bimaculata, capable of causing severe defoliation if unmanaged, can periodically occur through a substantial proportion of a plantation rotation. Some exotic insect pests not yet established in Australia, most notably Asian Gypsy Moth ( Lymantria dispar ), share the similar characteristic of imposing a threat for a substantial proportion of a plantation rotation. Managing such a threat is operationally complex and requires committing adequate resources to sustain a robust management system. However, the costs and benefits to the plantation owner of sustaining such a management system have not been quantified. The first step of such an analysis is to quantify the gains in additional wood yields from management that protects against severe defoliation of plantations. Forestry Tasmania has conducted considerable research to develop an Integrated Pest Management (IPM) program to protect its plantations from damaging populations of P. bimaculata, and has been using this leaf beetle IPM program since the early 2000s. The program has generated many years of operational records from leaf beetle population monitoring. These historical population monitoring data coupled with knowledge of the impact of defoliation by leaf beetles on tree growth were used to estimate how much wood volume has been saved by protecting the Forestry Tasmania plantation estate from damaging large leaf beetle populations over an entire rotation. The probability of above-threshold leaf beetle populations (defined as populations that cause severe defoliation, >50%, if uncontrolled) could be predicted from (1) plantation age (the likelihood of above-threshold populations peaks at age 4–5 years and declines to a low value by age 12 years), and (2) site-level leaf beetle risk (sites of high leaf beetle risk were at higher elevation and closer to native grassland than sites of low leaf beetle risk). Based on these relationships, the occurrence of above-threshold leaf beetle populations was predicted in Forestry Tasmania's 50 000 ha plantation estate between 2003 and 2034. The leaf beetle IPM program, through controlling these above-threshold populations, was then predicted to be able to avert losses of 2.18 million m 3 (9.4% of merchantable wood volume).